Undergraduate teaching in geriatric medicine: mapping the British Geriatrics Society undergraduate curriculum to Tomorrow's Doctors 2009 - Forrester-Paton, Calum; Forrester-Paton, Jayne; Gordon, Adam L.; Mitchell, Hannah K.; Bracewell, Nicola; Mjojo, Jocelyn; Masud, Tahir; Gladman, John R.F.; Blundell, Adrian (Oxford University Press, 2014)
Introduction: in 2008, the British Geriatrics Society (BGS) developed the Recommended Undergraduate Curriculum in Geriatric Medicine. This was subsequently mapped to the second edition of Tomorrows' Doctors (TD2, 2003). Following the publication of the third edition of Tomorrow's Doctors in 2009 (TD3), the mapping exercise was repeated to verify the extent to which the updated General Medical Council recommendations supported teaching in ageing and geriatric medicine.